Goal programming for sizing and allocation of a fleet of trucks in a mining company - Quiroz-Silva, Edmundo (2019)
Decision making in mining is a complicated process. Decisions regarding the sizing and allocation of the fleet of trucks to different mines, considering the compliance with production and the total objective cost, are of paramount importance to mining companies as this directly affects their profits. This document presents a model of goal programming (based on linear programming) to optimize mining operations in underground mining taking into account three goals: (a) To minimize deviations from the target production of different minerals, (b) to minimize the surplus of the total designated operating cost and (c) to maximize the use of concentrator plants’ maximum capacity. The model determines the number of trucks needed and provides the optimal allocation to each mine while addressing the goals and limitations of the mining operation. The proposed model was validated using real data from a Peruvian mining company.